Association of vitamin D status at birth with pulmonary disease morbidity in very preterm infants. Issue 5 (23rd December 2020) - Zhang, Xuefei; Luo, Kaiju; He, Xiaori; Chen, Pingyang
Abstract: Objective: We aimed to assess whether serum 25‐hydroxyvitamin D (25(OH)D) levels at birth are associated with pulmonary disease morbidities in very preterm infants. Methods: This prospective cohort analysis included 93 infants born before 32 weeks of gestation in the Second Xiangya Hospital of Central South University between March 2016 and February 2017. Participants were classified into three groups according to their 25(OH)D levels at birth. The groups were compared in terms of demographic variables and pulmonary disease morbidities. Results: The mean serum 25(OH)D level at birth was 35.7 ± 19.1 nmol/L, and 38 (40.9%), 31 (33.3%), and 24 (25.8%) infants had 25(OH)D levels of less than 25 nmol/L, 25–50 nmol/L, and more than or equal to 50 nmol/L, respectively. There was a statistically significant difference in neonatal respiratory distress syndrome (RDS) rates among the three groups (43.6% vs. 35.9% vs. 20.5%, p  = .029). The rates of bronchopulmonary dysplasia, apnea, respiratory failure, persistent pulmonary hypertension, and pulmonary hemorrhage did not differ significantly among the groups. Logistic analysis, adjusted for gestational age and birth weight, showed that a low serum 25(OH)D level (<50 nmol/L) was a risk factor for RDS (odds ratio, 0.195; p  = .017). Conclusion: There was a high prevalence of low 25(OH)D levels (<50 nmol/L) and an association between vitamin D status and RDS in very preterm infants. However, more research on this association is required.